Comparison of Antimicrobial Resistance among Commensal Escherichia coli Isolated from Retail Table Eggs Produced by Laying Hens from the Cage and Non-Cage Housing Systems in Western Australia - Hamid Reza Sodagari; Csaba Varga; Ihab Habib; Shafi Sahibzada (MDPI AG, 2023)
Antimicrobial resistance (AMR) has become a global public health concern in recent decades. Although several investigations evaluated AMR in commensal and pathogenic bacteria from different foods of animal origin in Australia, there is a lack of studies that compared AMR in commensal E. coli isolated from retail table eggs obtained from different laying hen housing systems. This study aimed to determine AMR and differences in AMR patterns among E. coli isolates recovered from retail table eggs sourced from caged and non-caged housing systems in Western Australia. Commensal E. coli isolates were tested for susceptibility to 14 antimicrobials using a broth microdilution method. Clustering analyses and logistic regression models were applied to identify patterns and differences in AMR. Overall, there were moderate to high frequencies of resistance to the antimicrobials of lower importance used in Australian human medicine (tetracycline, ampicillin, trimethoprim, and sulfamethoxazole) in the isolates sourced from the eggs of two production systems. All E. coli isolates were susceptible to all critically important antimicrobials except the very low level of resistance to ciprofloxacin. E. coli isolates from eggs of non-caged systems had higher odds of resistance to tetracycline (OR = 5.76, p < 0.001) and ampicillin (OR = 3.42, p ≤ 0.01) compared to the isolates from eggs of caged systems. Moreover, the number of antimicrobials to which an E. coli isolate was resistant was significantly higher in table eggs from non-caged systems than isolates from caged systems' eggs. Considering the conservative approach in using antimicrobials in the Australian layer flocks, our findings highlight the potential role of the environment or human-related factors in the dissemination and emergence of AMR in commensal E. coli, particularly in retail table eggs of non-cage system origin. Further comprehensive epidemiological studies are required to better understand the role of different egg production systems in the emergence and dissemination of AMR in commensal E. coli.